Social Environments, Genetics, and Black–White Disparities in Infant Mortality. Issue 6 (November 2015) - El‐Sayed, Abdulrahman M.; Paczkowski, Magdalena; Rutherford, Caroline G.; Keyes, Katherine M.; Galea, Sandro
Abstract Background Genes and environments often interplay to produce population health. However, in some instances, the scientific literature has favoured one explanation, underplaying the other, even in the absence of rigorous support. We examine parental race disparity on the risk of infant mortality to see if such an analysis might provide clues to understanding the extent to which genes and environment may shape perinatal risks. Methods We assessed parental racial disparities in infant mortality among singletons by analysing the risk of infant mortality among racially consonant vs. dissonant couples over time between 1989–1997 and 1998–2006 in the state of Michigan (n = 1 428 199). We calculated the degree of modification of the relation between maternal race and infant mortality by paternal race dynamically across the two time periods. Results Infant mortality among interracial couples decreased with time relative to white–white couples, while infant mortality among black–black couples increased with time after adjusting for socio‐economic, demographic, and prenatal care differences. The degree to which paternal black race strengthened the relation between maternal black race and higher infant mortality risk relative to white mothers increased with time throughout our study. Conclusions Evidence from these data suggests that environmental factors likely play the greater role in explaining the parental race disparity and risk of infant mortality.